1973
DOI: 10.1159/000208414
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of the Proliferative Activity of Erythroblasts in Untreated and Treated Acute Leukaemia

Abstract: In 7 cases of untreated and 2 cases of treated acute leukaemia (AL) the erythropoietic cell proliferation was studied by the combined method using AFeulgen-cytophotometry and autoradiography after labelling with 3H-TdR in vivo (1 h after intravenous injection) or in vitro. A proliferation disturbance was observed, which was almost limited to the early polychromatic erythroblasts, consisting of an accumulation of diploid and unlabelled cells and a decreased proportion of cells in S. This proliferation defect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…The disturbed cell proliferation leads to the hyperplasia and a 'shift to the left' (table II) of erythropoiesis. The morphologically normal erythropoiesis, however, has a reduced proliferative activity and is com parable with erythropoiesis in refractory anaemia with hyperplastic bone marrow (unpublished results) and with erythropoiesis in acute leukaemia [9,12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The disturbed cell proliferation leads to the hyperplasia and a 'shift to the left' (table II) of erythropoiesis. The morphologically normal erythropoiesis, however, has a reduced proliferative activity and is com parable with erythropoiesis in refractory anaemia with hyperplastic bone marrow (unpublished results) and with erythropoiesis in acute leukaemia [9,12].…”
Section: Discussionmentioning
confidence: 90%
“…Combined cytophotometric-autoradiographic investigations on erythropoiesis so far resulted in contradictory findings. Wickramasinghe et al [3] in one case of erythroleukaemia demonstrated an arrest of early polychromatic normoblasts in the premitotic phase, while in a second case Q ueisser et al [12] detected an increased percentage of proliferating erythroblasts in G,. Finally Crossen et al [2] in a third case found an arrest of cells in the S phase.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned initially there is cytogenetic evidence that the erythroblasts in acute mye loid leukaemia are of leukaemic origin [2,4,11,15,16] and studies with thymidine labelling [4,9,13,17,22] have indicated abnormal ki netic properties. It is interesting in this context to note that H uber et al [13] and Queisser et al [17] found low labelling indices of erythro blasts in AML but that in the present investigation high mitotic indices were found. Ernst et al [7] found a similar discrepancy between thymi dine-labelling indices and mitotic indices of erythroblasts in patients with AML and suggested that the low utilization of labelled thymidine might be a biochemical expression of 'leukaemicness' of the erythroid cells.…”
Section: Discussionmentioning
confidence: 88%
“…Recent cytogenetic studies have shown evidence of leukaemic involvement of the erythroblasts not only in erythroleukaemia (EL) but also in cases of acute granulocytic leukaemia [2,15,16). Re sults of kinetic investigations in acute leukaemia suggest that an ineffec tive erythropoiesis due to a defective maturation of the erythroblasts may be of importance to the development of anaemia [9,13,17).…”
mentioning
confidence: 99%
“…It has been suggested that a defective differentiation of erythroid pre cursors contributes to anaemia in AML [6,8,12]. It may be that the me galoblastic changes of the erythroblasts are morphologic signs of disturb ances in the DNA synthesis of the cells leading to an ineffective erythropoiesis and that the karyotypic changes occurring in the AML erythro blasts are of minor importance for the impaired function of the erythroid tissue.…”
Section: Discussionmentioning
confidence: 99%